Increasing the Accuracy of Measuring the Resistance of the Grounding System with an Electrodeless Method - Tugushi, Maia; Karasiev, Boris; Partskhaladze, Gizo; Loria, Madona; Chavleshvili, Gocha (International Journal of Engineering and Technology, 2018)
Recently, electrodeless methods of measuring the resistance of grounding devices have appeared, with the help of special clamps. But a large methodological error limits the possibility of their use, especially when rationing low resistances.Â The article shows the possibility to improve the accuracy of electrodeless measurement methods using commercially available measuring instruments.In electrical installations of telecommunication networks of buildings, structures and industrial enterprises, the form of the AC voltage signal of the industrial supply network ( 220V, 50/60Hz) can be differ greatly from the sinusoidal for short periods of time. The causes of distortions are usually associated with a sudden change in the network load [1], for example, when you turn on a powerful electric motor, furnace, welding machine, etc.The occurrence of impulse overvoltages and interference caused by electromagnetic effects (lightning, switching, radio frequency and others) on low-voltage networks, not only leads to failure of electrical installations, cables, switchboards, but also to damage the terminal equipment and malfunction. This is due, primarily, to the saturation of modern buildings and structures with information, telecommunications and other digital equipment, which has a very low level of protection against impulse overvoltages and interference. All this makes it necessary to carry out appropriate protective measures. To reduce interference, it is necessary to perform a separate (working) ground loop, the resistance of which must be measured and periodically monitored.There are devices that allow an electrodeless method to monitor and evaluate the resistance of the ground loop. But these devices have a greater measurement error than devices that measure the resistance of the earth electrode method.The article deals with existing instruments (CA6410, MZC-303E) which can evaluate the resistance of the earth electrode and the possibility of increasing the accuracy of the measurement with the help of special current clamps is shown. Using a predetermined value of neutral impedance, the measurement error of the calculated resistance of the earthing switch can be determined with great accuracy.Â